Effectiveness of a tutorial program in the self-regulation of High School students of a Confessional Private School - Mamani Quispe, Queleon Elmer (2017)
This study proposes a model of experiential intervention that allows High School students to self-regulate their behavior for the adequate personal development in the adolescence. The methodology of the research was mixed. Quantitative and qualitative data were collected, analyzed and linked to obtaining complementary information on the phenomenon under study. We used the quasi-experimental design with pre and posttest design when working with intact groups: control and experimental group. This methodology allows the treatment of the phenomenon from a holistic perspective, by detecting basic and relevant elements in different situations, studying the behaviors of students when confronted with moral situations of conflict with values, and in circumstances that show self-regulation of the behavior to determine the decision or disposition of the adolescents in a rational and autonomous way. The results obtained through the t-test showed that the program was effective in self-regulation of behavior with an average score of Control Group 100.70 and the Experimental Group corresponding to 129.30 and the significance level reflects a significant result (0.000 <0.05).